Endowment funds as a component of the financial mechanism of global and Kazakhstani higher educational institutions (Journal of Economic Research & Business Administration, 2021)
This article reflects one of the ongoing issues experienced by higher educational institutions – theformation of sustainable financial mechanisms to effectively influence the results of their activities aswell as to promote their strategic development, and to transition to the global market.Along with this, insufficient funding in the Republic of Kazakhstan affects the material and technicalbases of higher educational institutions, as well as the implementation of IT innovations within them.The formation of endowment funds could be a way to diversify educational institutions’ finance. Endowmentfunds funded by donations and are used by non-profit organizations for specific purposes, usuallyto fund significant educational, scientific, and community programs.The article contains an analysis of the existing endowment funds at educational institutions of theRepublic of Kazakhstan as well as foreign models of endowment funds. The process of endowmentfunds’ formation and their effectiveness indicators are considered as well. In addition, the article providesan analysis of global practices in operations of endowment funds and their implementation toKazakhstani conditions. Also, recommendations on the legislative regulation of endowment funds, taxbenefits, and other preferences on building relationships with potential and future donors were providedin this article. As a result of analysing endowment funds’ activities of the Republic of Kazakhstan, a numberof their effectivity factors were identified.Key words: endowment funds, financial mechanism, financing of higher educational institutions,fundraising, budgeting.